Agrobacterium-Mediated Transformation of Russian Commercial Plum cv. “Startovaya” (Prunus domestica L.) With Virus-Derived Hairpin RNA Construct Confers Durable Resistance to PPV Infection in Mature Plants - Sidorova, Tatiana; Mikhailov, Roman; Pushin, Alexander; Miroshnichenko, Dmitry; Dolgov, Sergey (Frontiers in Plant Science, 2019)
In modern horticulture Plum pox virus (PPV) imposes serious threats to commercial plantations of a wide range of fruit species belonging to genera Prunus. Given the lack of natural genetic resources, which display reliable resistance to PPV infection, there has been considerable interest in using genetic engineering methods for targeted genome modification of stone fruit trees to control Sharka disease caused by PPV. Among the many virus defense mechanisms, RNA interference is shown to be the most promising transgenic disease-control strategy in plant biotechnology. The present study describes the production of transgenic PPV resistant European plum ‘Startovaya’ (P.domestica L.) through the Agrobacterium-mediated transformation of in vitro leaf explants. Due to organogenesis from leaves, the established protocol allows the genetic engineering of the plum genome without losing clonal fidelity of original cultivar. Seven independent transgenic plum lines containing the self-complementary fragments of PPV-CP gene sequence separated by a PDK intron were generated using hpt as a selective gene and gusA as a reporter gene. The transformation was verified through the histochemical staining for β-glucuronidase activity, PCR amplification of appropriate vector products from isolated genomic DNA and Southern blot analysis of hairpin PPV-CP gene fragments. To clarify the virus resistance, plum buds infected by PPV-M strain were grafted onto one-year-old transgenic plants, which further were grown into mature trees in the greenhouse. As evaluated by RT-PCR, DAS-ELISA, Western blot, ImmunoStrip test and visual observations, GM plum trees remained uninfected over nine years. Infected branches that developed from grafted buds displayed obvious symptoms of Sharka disease over the years and maintained the high level of virus accumulation, whereby host transgenic trees had been constantly challenged with the pathogen. Since the virus was unable to spread to transgenic tissues, the stable expression of PPV-derived gene construct encoding intron-spliced hairpin RNAs provided a highly effective protection of plum trees against permanent viral infection. At the same time, this observation indicates the lack of the systemic spread of resistance from GM tissues to an infected plum graft even after years of joint growth.